Direct Financial Losses and Lived Experiences of Smallholder Pig Farmers in ASF-Affected Areas of Surigao del Sur, Philippines - Dargantes, Kassey Alsylle; Siton, Vincent Rafael; Ebora, Arianne; Daguro, Ted Aries; Angcos, Lowella; Dargantes, Alan (Universitas Airlangga, 2025)
Following the first reported African Swine Fever (ASF) outbreak in Surigao del Sur in 2020, subsequent outbreaks have had a significant impact on smallholder pig farms across the province. This study aimed to estimate the direct financial losses due to ASF and to describe the lived experiences of affected smallholder farmers, specifically their perceptions, livelihood impact, management responses, and emotional distress, one year after the outbreak. A total of 108 smallholder pig farmers from three ASF-affected municipalities were interviewed using validated survey tools. Financial losses were calculated using a deterministic approach with descriptive statistics, while qualitative data were examined using Colaizzi's descriptive phenomenological method. Results showed that the outbreak affected 819 farms and 29 villages across eight municipalities. Direct financial losses were estimated at USD 39,795.85, averaging USD 736.96 per household. Phenomenological data revealed six themes: ASF knowledge, misconceptions, perceptions of transmission, economic impact, and control efforts. Many farmers also reported emotional distress due to the outbreak. This study provides valuable insights to guide targeted interventions, emphasizing veterinary outreach, biosecurity education, and community support to enhance resilience and reduce vulnerability in smallholder pig production systems.